Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.3171/jns.1995.83.3.0503
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomized, double-blind trial of BQ-123 and bosentan for prevention of vasospasm following subarachnoid hemorrhage in monkeys

Abstract: Thirty-one monkeys were randomly divided into three groups to undergo baseline cerebral angiography followed by induction of subarachnoid hemorrhage by placement of autologous blood clot along the right-sided arteries of the anterior circle of Willis (Day 0). The monkeys were then given drug vehicle or one of two endothelin (ET) antagonists, BQ-123 (6 mg/kg/day) or bosentan (5 mg/kg/day) intracisternally. The BQ-123 was administered by continuous infusion from a subcutaneous pump and the bosentan was given by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 28 publications
1
34
1
1
Order By: Relevance
“…Several studies have found increased ET-1 concentrations in the cerebrospinal fluid of patients with cerebral vasospasm and during vasospasm in animal models of SAH. Numerous animal studies have documented the efficacy of ET receptor antagonists at preventing or alleviating experimental vasospasm (1,(27)(28)(29). Hemoglobin, and possibly ferrous hemoglobin specifically, is a prime candidate for the cause of vasospasm, and our results suggest that the NO scavenging effect may contribute to vasospasm both by removing vasodilating NO and by simultaneously increasing ET-1.…”
Section: Effect Of No On Et-1 Peptide Synthesis By Ferrous Hemoglobinmentioning
confidence: 58%
“…Several studies have found increased ET-1 concentrations in the cerebrospinal fluid of patients with cerebral vasospasm and during vasospasm in animal models of SAH. Numerous animal studies have documented the efficacy of ET receptor antagonists at preventing or alleviating experimental vasospasm (1,(27)(28)(29). Hemoglobin, and possibly ferrous hemoglobin specifically, is a prime candidate for the cause of vasospasm, and our results suggest that the NO scavenging effect may contribute to vasospasm both by removing vasodilating NO and by simultaneously increasing ET-1.…”
Section: Effect Of No On Et-1 Peptide Synthesis By Ferrous Hemoglobinmentioning
confidence: 58%
“…This discrepancy is all the more difficult to understand since it has been reported that ET antagonists inhibit vasospasm in primates (147,148) as well as in other species. By far the most significant increases of ET concern ET-1, only sporadic amounts of ET-3 being noted in one report (141).…”
Section: Presence Of Ets In Csf After Sahmentioning
confidence: 79%
“…Cerebral vasospasm is a major complication of human aneurysmal SAH gravely affecting outcome, but the underlying pathogenetic mechanism has remained unresolved and the treatment remains to be established. To investigate the pathophysiology and therapy of cerebral vasospasm, various animal models such as dogs [9][10][11][12]18], monkeys [1,6,7], rabbits [2,4,15], cats [17], and rats [3,8,16] have been used. While each model has its merits and demerits, by far the most popular model has been the canine SAH model first proposed by Varsos et al [18], designated the "two-hemorrhage" model.…”
Section: Dhhs Publication No [Nih] 85-23 Revised 1985)mentioning
confidence: 99%
“…The placement of an intrathecally indwelling catheter has already been reported in a monkey SAH model [7], where the indwelling catheter was used solely for the purpose of intrathecal drug administration as SAH was induced by the placement of a blood clot around the middle cerebral artery by craniotomy. Since we hypothesized the use of such catheters not only for drug administration but also for the induction of repeated SAH might improve the canine "twohemorrhage" model, we examined the feasibility of this technique in dogs in the present study.…”
Section: Dhhs Publication No [Nih] 85-23 Revised 1985)mentioning
confidence: 99%